PEMANFAATAN ANT COLONY OPTIMIZATION ALGORITHM UNTUK MASALAH OPTIMISASI TATA LETAK FASILITAS DAN MASALAH OPTIMISASI WAKTU-BIAYA - APRIANI , VERGINA
Construction site layout is the important factor that influences performance level of project. Design of layout is related to arrange the placement of facilities at the prepared location. Facility layout is designed to minimize the travel time between facilities, improve site safety, increase productivity, and decrease construction time and cost. In order to get a satisfactory result and maximize the return, both the client and the contractor would strive to optimize project duration and cost simultaneously. In this final project, Ant Colony Optimization (ACO) algorithm will be utilized to solve facility layout optimization problem and time-cost optimization problem in a project construction. ACO is an optimization method that mimics the foraging behaviour of real ants for finding solutions of combinatorial optimization problem, in this case facility layout and time-cost problem. The effectiveness of ACO method can provide the alternative arrangements of facility layout and combinations of optimal time-cost.